CONCEPT OF GENDER AND GENDER EQUALITY - Ikromjon Yuldashov, PhD. (Journal Park Publishing, 2023)
Within the framework of gender strategy, the concept of gender equality means equal rights and opportunities of women and men in all spheres of society's life and activities, including politics, economy, law, culture, education, science, and sports. This article is a pedagogical study of gender equality and the content and relevance of the concept of gender
Keywords: society, justice, equality, gender, gender equality, Family, Women's right, social protection.